ФЛОРИСТИЧНI ТА ФАУНIСТИЧНI ЗМIНИ НА КРИМСЬКОМУ ШЕЛЬФI ЧОРНОГО МОРЯ ПІСЛЯ 1995 – 1998 РР - Заїка, В. Є.; Болтачов, О. Р.; Зуєв, Г. В.; Ковальов, О. В.; Мільчакова, Н. О.; Сергеєва, Н. Г. (Marine Ecological Journal, 2023)
Analyses of long-term changes of biodiversity in the Crimean shelf have suggested that a peak in the reduction of marine biota and the decrease of species number were registered from the end of 1980s to the middle of 1990s. After 1995 – 1998, a good deal of data was reported on health of benthic and pelagic communities. The increase of the species number is known not only in the Crimean shelf zone, but also in Sevastopol Bay where eutrophication was strong. Documented data on different groups of marine plants and animals, zoo- and phytoplankton, benthos, fishes and dolphins are widely presented in the paper.